2015
DOI: 10.1097/bot.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Multicenter Trial Comparing Clinical Outcomes of Patients Treated Surgically With a Static or Dynamic Implant for Acute Ankle Syndesmosis Rupture

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
204
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(220 citation statements)
references
References 34 publications
5
204
2
9
Order By: Relevance
“…The use of these devices was not evaluated in our meta-analysis; however, this is an interesting topic for future research (25).…”
Section: Discussionmentioning
confidence: 93%
“…The use of these devices was not evaluated in our meta-analysis; however, this is an interesting topic for future research (25).…”
Section: Discussionmentioning
confidence: 93%
“…A prospective, randomized control trial demonstrated better clinical and radiographic outcomes with a dynamic device, with improved maintenance of reduction and lower reoperation rate. 131 Despite the increased cost of the implant, the decreased need for hardware removal may confer cost-effectiveness to this technique. Lastly, one can consider hybrid fixation with a screw and suture button construct for severe diastasis or large athletes.…”
Section: Dynamic Fixationmentioning
confidence: 99%
“…The literature on dynamic fixation is evolving, with the recent high-level literature suggesting improved outcomes without the need for hardware removal. 131 The most pertinent, technical aspect of surgical treatment is the accuracy of the reduction. This aspect has been shown to be the most important independent predictor of clinical outcomes and vital in avoiding posttraumatic arthrosis.…”
Section: Surgeon Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some limited investigations have attempted to compare dynamic suture button fixation with syndesmotic screw fixation [54,[57][58][59][60][61][62]. Westermann et al performed a cadaveric study to see if there was a difference in the malreduction of syndesmotic injuries when comparing screw fixation with tightrope fixation [58].…”
Section: Operative Treatment For Isolated Syndesmotic Injuriesmentioning
confidence: 99%